1994
DOI: 10.1111/j.1365-2125.1994.tb04393.x
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the systemic activity of single doses of inhaled fluticasone propionate in healthy volunteers [see comments]

Abstract: 1. The systemic effects of inhaled fluticasone propionate (FP), administered via Diskhaler, on the hypothalamo‐pituitary‐adrenal (HPA) axis were assessed primarily by measuring plasma cortisol at frequent intervals for 20 h after drug administration. 2. FP showed a dose‐ related suppression of plasma cortisol measured as area under the plasma cortisol vs time curve (AUC 0‐20). The cortisol suppression (expressed as % fall from placebo) was 8, 19, and 28% for single doses of 250 micrograms FP, 500 micrograms FP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 13 publications
2
49
1
Order By: Relevance
“…This may help to explain why FP causes more adrenal suppression than BUD, in particular during steady state daily dosing [19 -22]. During single-dose studies, accumulation of lipophilic compounds does not occur and systemic effects may be less clear [23]. Studies on systemic side effects of ICS9s, are therefore best performed during steady state dosing.…”
Section: What Is the Bioavailability Of Inhaled Corticosteroids?mentioning
confidence: 99%
“…This may help to explain why FP causes more adrenal suppression than BUD, in particular during steady state daily dosing [19 -22]. During single-dose studies, accumulation of lipophilic compounds does not occur and systemic effects may be less clear [23]. Studies on systemic side effects of ICS9s, are therefore best performed during steady state dosing.…”
Section: What Is the Bioavailability Of Inhaled Corticosteroids?mentioning
confidence: 99%
“…The number of subjects to be used in this study was estimated using historical 20 h mean plasma cortisol data [16]. With 21 subjects, a difference in plasma cortisol suppression from placebo of 13% between FP and BUD could be detected, with 80% power at the 0.05 level.…”
Section: Discussionmentioning
confidence: 99%
“…However, three recent controlled studies have suggested that FP may have a greater systemic activity than BUD (DH vs TBH [16,17], pMDIs [18]). In order to make a correct assessment of the relative systemic activity on a milligram for milligram nominal dose basis, dose-responses of both drugs should be established, using sensitive parameters to determine systemic activity.…”
mentioning
confidence: 99%
“…The study of Grahnen et al [1] as reported, is deficient in design in that comparisons are made between single and multiple doses and a dose-response of one drug (fluticasone propionate (FP)) compared with just single doses of another (budesonide). The only relevant comparisons would have been between either equally effective doses, or equal weight single and multiple doses of both drugs.…”
Section: Systemic Effects Of Glucocorticoids-a Responsementioning
confidence: 99%